Growth Diversity of Nyamplung (Calophyllum inophyllum) Seedling from Sumenep, Madura - Aam Aminah; NFN Danu; Yulianti Bramasto (Jurnal Perbenihan Tanaman Hutan, 2019)
One source of potential biofuel feedstock in Indonesia is nyamplung (Calophyllum inophyllum). Superiority of nyamplung is having a high oil content of 40 percent ―73percent. The purpose of this study was to identify growth variation and heritability value for the height and diameter characters of nyamplung seedlings at six months old from 26 parent trees from Sumenep, Madura. The research used Randomized Complete Block Design with 26 families from Sumenep Madura as treatment, each treatment consisted of 3 replications,each replication consisted of 8 seedlings, so the number of seedlings used was 624 seedlings. The results showed that there were diversity in growth (height and diameter) at the level of nyamplung seedling from Sumenep, Madura. The height and diameter of nyamplung seedlings of 26 families tested varied between 12.52 cm ― 21.27 cm and 3.04 mm ―4.54 mm. Individual heritability values for seedling height and diameter are 0.27 and 0.16, while family heritability values are 0.65 for height and 0.52 for diameter